A novel genomic signature reclassifies an oral cancer subtype. Issue 10 (9th June 2015) - Samman, Manar; Wood, Henry M.; Conway, Caroline; Stead, Lucy; Daly, Catherine; Chalkley, Rebecca; Berri, Stefano; Senguven, Burcu; Ross, Lisa; Egan, Philip; Chengot, Preetha; Ong, Thian K.; et al.
<x xml:space="preserve">Abstract</x> Verrucous carcinoma of the oral cavity (OVC) is considered a subtype of classical oral squamous cell carcinoma (OSCC). Diagnosis is problematic, and additional biomarkers are needed to better stratify patients. To investigate their molecular signature, we performed low‐coverage copy number (CN) sequencing on 57 OVC and exome and RNA sequencing on a subset of these and compared the data to the same OSCC parameters. CN results showed that OVC lacked any of the classical OSCC patterns such as gain of 3q and loss of 3p and demonstrated considerably fewer genomic rearrangements compared to the OSCC cohort. OVC and OSCC samples could be clearly differentiated. Exome sequencing showed that OVC samples lacked mutations in genes commonly associated with OSCC (TP53, NOTCH1, NOTCH2, CDKN2A and FAT1). RNA sequencing identified genes that were differentially expressed between the groups. In silico functional analysis showed that the mutated and differentially expressed genes in OVC samples were involved in cell adhesion and keratinocyte proliferation, while those in the OSCC cohort were enriched for cell death and apoptosis pathways. This is the largest and most detailed genomic and transcriptomic analysis yet performed on this tumour type, which, as an example of non‐metastatic cancer, may shed light on the nature of metastases. These three independent investigations consistently show substantial differences between the cohorts. Taken together, they lead to the conclusion that OVC is not a subtype of OSCC, but should be classified as a distinct entity.